Virtual touch tissue quantification (VTQ) in the diagnosis of thyroid nodules with coexistent chronic autoimmune Hashimoto's thyroiditis: A preliminary study. Issue 2 (February 2015) - Han, Ruijun; Li, Fenghua; Wang, Yan; Ying, Zhiqiang; Zhang, Yun
Highlights: Virtual Touch Tissue Quantification could provide quantitative measurements to estimate tissue stiffness noninvasively. Severity of Hashimoto's thyroiditis could affect stiffness of extra-nodular thyroid tissue significantly. Shear wave velocity of malignant nodules significantly higher than that of benign nodules. Acoustic Radiation Force Impulse imaging is useful in differential diagnosis between malignant/benign thyroid nodules with HT. Abstract: Objectives: This study aimed at detecting whether Virtual Touch Tissue Quantification (VTQ) could be applied to differentiate between benign and malignant thyroid nodules with chronic autoimmune Hashimoto's thyroiditis (HT). Methods: Convenient ultrasound and Virtual Touch Tissue Quantification were performed in 118 patients with 140 thyroid nodules with histology results. The HT group consisted of 46 patients with 58 nodules. The non-HT group consisted of 72 patients with 82 nodules. Results: The stiffness of extra-nodular thyroid tissue could be significantly affected by the severity of chronic autoimmune thyroiditis. The shear wave velocity of thyroid benign nodules and malignant nodules did not significantly differ in the HT group as compared with the non-HT group (benign nodules: 2.13 ± 0.32 m/s vs 1.98 ± 0.48 m/s, P  = 0.122; malignant nodules: 3.32 ± 0.77 m/s vs 3.30 ± 0.74 m/s, P  = 0.894). In two groups, the shear wave velocity of malignant nodules is significantly higher than that of benign nodules (HT group: 3.32 ± 0.77 m/s vs 2.13 ± 0.32 m/s; non-HT group: 3.30 ± 0.74 m/s vs 1.98 ± 0.48 m/s, P  < 0.001). The best cutoff point for shear wave velocity between malignant and benign thyroid nodules was 2.75 m/s. Conclusions: Virtual Touch Tissue Quantification technology could be performed in the differential diagnosis between malignant thyroid nodules and benign thyroid nodules independently from the coexistence of chronic autoimmune thyroiditis.